ARTISTIC CONTENT OF THE PEARLS OF THE CHURCH ARCHITECTURE OF BOIKIVSHCHYNA - Pisio, С. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
Boikivshchyna has been famous for its artistic traditions since ancient times. Works of folk painting of the 16th –18th centuries have been preserved in the Boikivshchyna region. They belong to the complex of unique monuments of the Ukrainian national artistic culture. The traditional decorative art of Boikivshchyna: embroidery, wood carving, decorating clothes, painting Easter eggs – have their own unique character. Architecture takes a prominent position in the cultural activities of local population and has brought its universal recognition. And this is quite natural, because the area of Boikivshchyna region has been covered by forest from immemorial time proving wood as an excellent building material. Folk craftsmen built houses with galleries, water mills, churches, bell towers, which are now considered masterpieces of folk architecture. Over centuries, a unique Boiky style has been developing, which reflects ingenuity, observation, aesthetic tastes and preferences of the builders. The use of wood contributed to development of its artistic processing and technology. Ancient buildings impress with their appearance, successful observance of proportions, always appropriate decorative decoration, expediency and rationality. The best examples of architecture have withstood the test of time and become monuments of culture testifying the high skills and artistic taste of their creators. Wooden temples are works of architectural perfection that best identify Ukrainians as a nation. Boiky sacred architecture is distinguished by picturesqueness, proportionality, a good ratio of masses and forms, mastery of material processing. On the ethnic territory of the Ukrainian Carpathians, the so-called type of “Boiky churches” was formed. It is a three-part and three-story church, in which the log cabins of the sanctuary, nave and babinets (forecourt) are covered with tented finishes with many folds. Despite the fact that there were different schools of construction of wooden churches in different regions, the principles of their construction are the same. The Boiky architecture is majestic in terms of the originality and uniqueness of the Ukrainian people and the world heritage of artistic achievements.